Dietary tryptophan intervention on growth and stress of Asian seabass, Lates calcarifer reared in recirculating aquaculture system - Kalidoss, Manikandan; Felix, Nathan; Prabu, Elangovan (Journal of Fisheries, 2026)
The rapid expansion of recirculating aquaculture system (RAS) aquaculture demands precise dietary strategies. Determining optimal tryptophan levels and understanding their combined effects on growth, blood responses, and stress regulation in Asian seabass remain limited. Addressing this knowledge gap, an experiment was conducted to evaluate the effects of L-tryptophan supplementation on growth, hematobiochemical responses and stress regulation of Asian seabass in RAS. Five isonitrogenous and isocaloric treatment diets were formulated to contain graded levels of L-tryptophan at 0.47 (T1), 0.53 (T2), 0.59 (T3), 0.66 (T4) and 0.72% (T4) of diet. At the end, an increase was observed in the growth of fish fed the T1 diet, after which no variation was observed. Dietary L-tryptophan had no effect on FCR across all the diet groups. Second order polynomial regression analysis of weight gain against dietary tryptophan levels indicated that the dietary tryptophan requirement for Asian seabass reared in RAS was 0.61% of the diet. No differences were observed in whole body composition and haematological responses among the treatment groups. Cholesterol and HDL-C levels followed trend similar to the growth performance. Cortisol level was significantly lowered in T1 than the control, whereas no variation was observed among other groups. Second order polynomial regression analysis of HDL-C and cortisol against dietary tryptophan levels showed that the dietary tryptophan requirement were 0.61% and 0.62% of the diet respectively. Overall, L-tryptophan at 0.61–0.62% maximizes growth, stress responses, and tryptophan–serotonin–cholesterol axis regulation in Asian seabass in RAS culture systems, optimizing performance.